Have this sum have close form $$f(n)=\sum_{k=0}^{n-1}\left(\left(\sum_{i=0}^{k}(-1)^i\binom{n}{i}\right)\cdot\left(‌​\sum_{j=k+1}^{n}(-1)^j\binom{n}{j}\right)\right)$$

Maybe this sum can use integral to solve it? Thank you

  • $\begingroup$ Note that David H answered first, I just added some extra justification. $\endgroup$ – robjohn Aug 8 '14 at 8:13

I've simply added a justification of the first identity in David H's answer.

Assume that $n\ge1$, so that $\binom{n-1}{n}=0$. $$ \begin{align} \sum_{j=0}^k(-1)^j\binom{n}{j} &=\sum_{j=0}^k(-1)^j\left[\binom{n-1}{j}+\binom{n-1}{j-1}\right]\\ &=\sum_{j=0}^k(-1)^j\binom{n-1}{j}-\sum_{j=0}^{k-1}(-1)^j\binom{n-1}{j}\\ &=(-1)^k\binom{n-1}{k}\tag{1} \end{align} $$ Using $k=n$ in $(1)$ yields $$ \begin{align} \sum_{j=0}^n(-1)^j\binom{n}{j} &=(-1)^n\binom{n-1}{n}\\ &=0\tag{2} \end{align} $$

Therefore, using Vandermonde's Inequality and $(1)$ and $(2)$ gives $$ \begin{align} &\sum_{k=0}^n\left(\sum_{i=0}^k(-1)^i\binom{n}{i}\right)\left(\sum_{j=k+1}^n(-1)^j\binom{n}{j}\right)\\ &=\sum_{k=0}^n(-1)^k\binom{n-1}{k}(-1)^{k+1}\binom{n-1}{k}\\ &=-\sum_{k=0}^n\binom{n-1}{k}\binom{n-1}{n-1-k}\\ &=-\binom{2n-2}{n-1}\tag{3} \end{align} $$

| cite | improve this answer | |

This sum is actually quite tame if you take it step by step.

The sum comprising the first factor is:


And since $\sum_{j=0}^{n}(-1)^j\binom{n}{j}=0$, we immediately find the sum in the second factor to be:


Hence, the sum for $f(n)$ can be written as a single finite binomial sum whose values are well known to be the (negatives of the) central binomial coefficients:


| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.